Acute disseminated encephalomyelitis and routine childhood vaccinations – a self-controlled case series. Issue 8 (3rd August 2021) - Martin, T. J.; Fahey, M.; Easton, M.; Clothier, H. J.; Samuel, R.; Crawford, N. W.; Buttery, J. P.
ABSTRACT: Acute disseminated encephalomyelitis (ADEM) is an autoimmune, central nervous system demyelinating disorder that follows antecedent immunologic challenges, such as infection or vaccination. This study aimed to investigate the potential association between routine childhood vaccinations and ADEM. Children under 7 years of age admitted to the two tertiary level pediatric hospitals in Victoria, Australia with ADEM from 2000–2015 had their clinical information linked to vaccination records from the Australian Childhood Immunization Register. Chart review was undertaken utilizing the Brighton Collaboration ADEM criteria. The self-controlled case-series (SCCS) methodology was employed to determine the relative incidences of ADEM post-vaccination in two risk intervals: 5–28 days and 2–42 days. Forty-six cases were eligible for SCCS analysis with a median age of 3.2 years. Of the forty-six cases, three were vaccine proximate cases and received vaccinations 23, 25 and 28 days before ADEM onset. Two vaccine proximate cases received their 4-year-old scheduled vaccinations (MMR and DTPa-IPV) and one vaccine proximate case the 1-year old scheduled vaccinations (MMR and Hib-MenC). The relative incidence of ADEM during the narrow and broad risk intervals were 1.041 (95% CI 0.323–3.356, p = 0.946) and 0.585 (95% CI 0.182–1.886, p = 0.370) respectively. Sensitivity analyses did not yield any substantial deviations. These results do not provide evidence of an association between vaccinations routinely provided to children aged under 7 years in Australia and the incidence of ADEM. However, these results should be interpreted with caution as the number of ADEM cases identified was limited and further research is warranted.